Application of two novel anionic peroxidases from Raphanus sativus L. var niger roots in labeling antibodies and developing an enzyme-linked immunosorbent assay - Hooman Askari; Ali Nabati; Aliasghar Rahimian; Mahdi Aminian (Heliyon, 2025)
HRP, or horseradish peroxidase, is a reporter enzyme with extensive use in biotechnological applications. We previously reported the purification and characterization of two anionic peroxidases from Raphanus sativus L. var niger (black radish) roots. Here, we evaluated the applicability of these two novel peroxidases as alternatives to traditional horseradish peroxidase (HRP). The two novel peroxidases (BRP-A and BRP-B) and HRP were conjugated to IgY polyclonal antibodies by chemical methods based on the use of sodium periodate and cyanuric chloride. Moreover, the applicability of BRP-A and BRP-B in immunoassays was investigated by comparing the signal generated by these novel peroxidases in ELISA with HRP conjugates. Additionally, the limit of detection (LOD) was calculated for BRP-A, BRP-B, and HRP conjugates. Finally, the thermal stability of peroxidase antibody conjugates at 37 °C and 4 °C was compared. The peroxidase antibody conjugates prepared by the periodate method generated a much stronger signal than those prepared by the cyanuric chloride method. The signal obtained by BRP-A and BRP-B conjugates was much lower compared to the commercial HRP enzyme. The limit of detection was found to be 385.71, 213.75, and 43.6 ng per well for BRP-A, BRP-B, and HRP conjugates prepared by the periodate method, respectively. However, for conjugates prepared by the cyanuric chloride method, the limit of detection could only be estimated for HRP since BRP-A and BRP-B had an extremely low signal-to-noise ratio. All peroxidase conjugates had comparable thermal stability at 37 °C and 4 °C.